Kinematic patterns associated with the vertical force produced during the eggbeater kick - Oliveira, N.; Chiu, C.-Y.; Sanders, R. H. (Journal of Sports Sciences, 2015)
The purpose of this study was to determine the kinematic patterns that maximized the vertical force produced during the water polo eggbeater kick. Twelve water polo players were tested executing the eggbeater kick with the trunk aligned vertically and with the upper limbs above water while trying to maintain as high a position as possible out of the water for nine eggbeater kick cycles. Lower limb joint angular kinematics, pitch angles and speed of the feet were calculated. The vertical force produced during the eggbeater kick cycle was calculated using inverse dynamics for the independent lower body segments and combined upper body segments, and a participant-specific second-degree regression equation for the weight and buoyancy contributions. Vertical force normalized to body weight was associated with hip flexion (average, r = 0.691; maximum, r = 0.791; range of motion, r = 0.710), hip abduction (maximum, r = 0.654), knee flexion (average, r = 0.716; minimum, r = 0.653) and knee flexion-extension angular velocity (r = 0.758). Effective orientation of the hips resulted in fast horizontal motion of the feet with positive pitch angles. Vertical motion of the feet was negatively associated with vertical force. A multiple regression model comprising the non-collinear variables of maximum hip abduction, hip flexion range of motion and knee flexion angular velocity accounted for 81% of the variance in normalized vertical force. For high performance in the water polo, eggbeater kick players should execute fast horizontal motion with the feet by having large abduction and flexion of the hips, and fast extension and flexion of the knees.